Pengaruh Tambahan Penghasilan Pegawai ASN dalam Meningkatkan Kinerja Pegawai: Studi Kasus pada BPPRD Kabupaten Muaro Jambi Tahun 2026 - Vera Yusnita; Deby Aisyah Rj Nur; Novi Peramasari (Kajian Ekonomi dan Akuntansi Terapan, 2026)
The success of an organization is closely related to the quality of its human resources. In government institutions, Civil Servants (ASN) are expected to perform professionally, competently, and efficiently in delivering public services and achieving organizational objectives. One of the strategies implemented by local governments to enhance employee motivation and performance is the provision of Additional Employee Income (Tambahan Penghasilan Pegawai/TPP). This study aims to analyze the effect of Additional Employee Income (TPP) on employee performance at the Regional Revenue and Retribution Management Agency (BPPRD) of Muaro Jambi Regency. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees of BPPRD Muaro Jambi Regency and analyzed using SPSS version 22.0. The analytical techniques included validity testing, reliability testing, simple linear regression analysis, and hypothesis testing to examine the relationship between TPP and employee performance. The results indicate that TPP has a positive and significant effect on employee performance. The coefficient of determination shows that TPP contributes 72.3% to employee performance, while the remaining 27.7% is influenced by other factors not examined in this study. These findings suggest that TPP serves as an effective incentive mechanism for improving employee motivation, productivity, and overall performance among civil servants within the organization.